PRODUCTION AND CHARACTERIZATION OF NOVEL FIBRINOLYTIC ENZYME FROM DIFFERENT SOIL FUNGAL SP. - RASHMI B.S.,; LINY P, (International Journal of Pharma and Bio Sciences, 2013)
Different fungal species, Aspergillus niger, Aspergillus flavus and Pencillium notatum selected for the production of extracellular fibrinolytic enzymes, Production rate was enhanced by using different carbon source where maltose increased the production rate of enzymes 2.4mg/ml in Aspergillus niger, 2.2mg/ml Aspergillus flavus and glucose 2.2mg/ml in Pencillium notatum. Enzyme was fractionated using ammonium sulfate fractionation, different characteristic studies like protease activity showed 1.4units/mg of proteins in Aspergillus niger, 1.0 units/mg of proteins in Aspergillus flavus, 1.3units/mg of proteins in Penicillium notatum. Fibrinplate method showed 200 µg/ml, 600 µg/ml, 240 µg/ml in Aspergillus niger, Aspergillus flavus, Penicillium notatum respectively and anticoagulation clotting time assay showed 25, 20, 15 min delay in clotting activity in Aspergillus niger, Penicillium notatum, Aspergillus flavus respectively. The Protein bands found on SDS-PAGE for fibrinolytic enzymes from different fungal sp were approximately 14kD from Penicillium notatum, 27kD from Aspergillus niger, 26kD from Aspergillus flavus. The current research showed fibrinolytic enzyme enhancement in maltose and glucose and its characterization specified that be a novel method for yield enhancement.